Triplet Therapy, Transplantation, and Maintenance until Progression in Myeloma - Richardson, Paul G.; Jacobus, Susanna J.; Weller, Edie A.; Hassoun, Hani; Lonial, Sagar; Raje, Noopur S.; Medvedova, Eva; McCarthy, Philip L.; Libby, Edward N.; Voorhees, Peter M.; Orlowski, Robert Z.; Anderson, Larry D.; et al. (The New England journal of medicine, 2022)
In a large, multinational, randomized trial, continuous lenalidomide maintenance therapy after triplet therapy (lenalidomide, bortezomib, and dexamethasone) and autologous stem-cell transplantation resulted in longer progression-free survival than triplet therapy alone.